1994
DOI: 10.1152/jn.1994.72.4.1464
|View full text |Cite
|
Sign up to set email alerts
|

Neurokinin 1 and 2 antagonists attenuate the responses and NK1 antagonists prevent the sensitization of primate spinothalamic tract neurons after intradermal capsaicin

Abstract: 1. Activation of neurokinin receptors contributes to the excitation of many dorsal horn neurons by cutaneous sensory stimuli, particularly noxious stimuli. In the present study we investigate the role of neurokinin receptors in the activation of primate spinothalamic tract (STT) neurons by cutaneous mechanical stimuli and by intradermal injection of capsaicin. This was done by testing the responses of these neurons to a battery of cutaneous stimuli before and during infusion by microdialysis of antagonists sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
47
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(55 citation statements)
references
References 0 publications
7
47
0
1
Order By: Relevance
“…Dougherty and Willis (1992) gave intradermal capsaicin to monkeys and showed 1) that discharge rate of second-order neurons in the DH increased after injection and 2) an increase in release of the excitatory amino acids glutamate and aspartate. They also found an increase in activation of NK1 receptors on second-order neurons, which, they hypothesized, might be contributing to the sensitization (Dougherty et al, 1994).…”
Section: A Animalsmentioning
confidence: 90%
“…Dougherty and Willis (1992) gave intradermal capsaicin to monkeys and showed 1) that discharge rate of second-order neurons in the DH increased after injection and 2) an increase in release of the excitatory amino acids glutamate and aspartate. They also found an increase in activation of NK1 receptors on second-order neurons, which, they hypothesized, might be contributing to the sensitization (Dougherty et al, 1994).…”
Section: A Animalsmentioning
confidence: 90%
“…48 Blockade of spinal NK1r not only attenuated spinothalamic neuron activation following capsaicin injection in the paw but also prevented sensitization to post-capsaicin mechanical stimuli. 49 Similarly, multibarrel electrode recording form dorsal horn neurons showed that the activity of SP-sensitised dorsal horn neurons receiving afferent noxious input from the periphery was reduced by specific NK1 r antagonist-the study reports on the critical role played by SP and NK1r in pain from joints. 50 Recently, the intrathecal SP-saporin complex has been observed to relieve facet joint pain and bone cancer pain.…”
Section: Nk1 Receptor and Nociceptionmentioning
confidence: 94%
“…Interestingly, recent studies have shown that CP96345 (a non-peptide NK-1 receptor antagonist) has anti-nociceptive effects in the formalin and capsaicin tests (Sakurada, Katsumata, Yogo, Tan-No, Sakurada & Kisara, 1993). Although this drug also has antagonist effects on Ca2P channels (Schmidt, McLean & Heym, 1992) the involvement of the NK-1 receptor in nociceptive mechanisms is supported by results based on the specific antagonist GR 82334 (Dougherty, Palecek, Paleckova & Willis, 1994). Metabotropic glutamate receptors are thought to play a role in modulation of synaptic transmission and neuronal excitability in the brain and contribute to regulate neuronal networks (Pin & Duvoisin, 1995) including nociceptive circuits in the spinal cord (Meller, Dykstra & Gebhart, 1993;Young, Fleetwood-Walker, Mitchell & Munro, 1994;Boxall, Thompson, Dray, Dickenson & Urban, 1996).…”
Section: Controlmentioning
confidence: 99%